The Music Field - Hajjar, Zaidoun (2020)
Using Pierre Bourdieu’s theories of Habitus, Capital, and Field, this paper will attempt to locate the "music field" through tackling the case of peripheral Syrian musicians that have been displaced to the core cultural spaces in Berlin. This thesis will also investigate how cultural capital allows newcomers to negotiate with dominant players within the cultural field, to gain legitimacy through countering processes of labeling and characterization. Moreover, music has proved to assist the process of social integration, through communication, increased interactions, building social networks as well as alleviating language and cultural borders.